Nove strukturne in funkcijske preiskavne metode za zgodnje odkrivanje glavkoma - Rekič, Andreja (Medicinski razgledi, 2006)
Glaucoma is a chronic progressive optic neuropathy. Glaucoma is the second leading cause of irreversible blindness. Therefore, detection of structural optic nerve head and retinal nerve fiber layer changes and consequent visual field loss in its early stages is important. This paper describes the fundamentals, strengths and limitations of new structural and functional testsfor the early detection of glaucoma. Comparison between the tests is presented, and an analysis of their use in clinical practice is made. Longitudinal studies are needed to determine the actual use of the new tests in clinical practice.
Keywords: Elektroretinografija; Glaucoma; Glavkom; Diagnosis; Mikroskopija konfokalna; Perimetry; Electroretinography; Oftalmoskopija; Ophthalmoscopy; Perimetrija; očesne bolezni; Microscopy, Confocal; diagnostične metode; diagnostika